2014
DOI: 10.1523/jneurosci.4985-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

The Shape of Dendritic Arbors in Different Functional Domains of the Cortical Orientation Map

Abstract: The neocortex is organized into macroscopic functional maps. However, at the microscopic scale, the functional preference and degree of feature selectivity between neighboring neurons can vary considerably. In the primary visual cortex, adjacent neurons in iso-orientation domains share the same orientation preference, whereas neighboring neurons near pinwheel centers are tuned to different stimulus orientations. Moreover, several studies have found greater orientation selectivity in iso-orientation domains tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The discovery of this unique organization enabled comparisons between homogeneous (domains) and heterogeneous (pinwheel) regions with respect to the orientation preference of local populations of neurons. [19][20][21][22][23][24][25][26][27] Using this technique, our work and the work of others have shown that pinwheels in the primary visual cortex correlate to poorer orientation selectivity of their component neurons as compared to domain regions. [28][29][30][31] This lower selectivity can occur specifically for optimally sized classical receptive field (CRF) stimuli, where the relatively small stimulus size elicits the maximum response, and where the driving mechanisms are largely feedforward and local cortical circuits.…”
Section: Introductionmentioning
confidence: 62%
“…The discovery of this unique organization enabled comparisons between homogeneous (domains) and heterogeneous (pinwheel) regions with respect to the orientation preference of local populations of neurons. [19][20][21][22][23][24][25][26][27] Using this technique, our work and the work of others have shown that pinwheels in the primary visual cortex correlate to poorer orientation selectivity of their component neurons as compared to domain regions. [28][29][30][31] This lower selectivity can occur specifically for optimally sized classical receptive field (CRF) stimuli, where the relatively small stimulus size elicits the maximum response, and where the driving mechanisms are largely feedforward and local cortical circuits.…”
Section: Introductionmentioning
confidence: 62%
“…Using two-photon imaging, Levy et al 44. found no relationship between the geometry of the dendritic arbour and the local homogeneity in the orientation map, suggesting that all layer 2/3 neurons integrate inputs similarly from all their neighbours.…”
Section: Resultsmentioning
confidence: 99%
“…This anatomical organization has significant implications for cortical development and imposes restrictions on the connectivity of cells within the map (Alexander & Leeuwen, ), partly because the dendritic fields of the neurons within the cortex tend to be near‐circular wherever they are positioned in the map (Martin & Whitteridge, ; Levy et al ., ). Therefore, local connections at pinwheel centres occur between neurons with many orientation preferences, whereas connections in iso‐orientation zones are between neurons with similar orientation preference (primate: Malach et al ., ; cat: Levy et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Neurons with selectivity for similar stimulus features are clustered together (orientation: Hubel & Wiesel, , ; ocular dominance: Blasdel & Salama, ; Ts'o et al ., ; Kara & Boyd, ; binocular disparity: Kara & Boyd, ; spatial frequency: Hübener et al ., ; Kim et al ., ; Issa et al ., ; Sirovich & Uglesich, ; Yu et al ., ; Nauhaus et al ., ; surround suppression: Vanni & Casanova, ). This anatomical organization has significant implications for cortical development and imposes restrictions on the connectivity of cells within the map (Alexander & Leeuwen, ), partly because the dendritic fields of the neurons within the cortex tend to be near‐circular wherever they are positioned in the map (Martin & Whitteridge, ; Levy et al ., ). Therefore, local connections at pinwheel centres occur between neurons with many orientation preferences, whereas connections in iso‐orientation zones are between neurons with similar orientation preference (primate: Malach et al ., ; cat: Levy et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation